Answer:
a)![y=\dfrac{13x}{16}-\dfrac{129}{16}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B13x%7D%7B16%7D-%5Cdfrac%7B129%7D%7B16%7D)
b)![y = \dfrac{13x}{16}+ \dfrac{37}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B13x%7D%7B16%7D%2B%20%5Cdfrac%7B37%7D%7B2%7D)
Step-by-step explanation:
Given two points:
and ![T(-8,12)](https://tex.z-dn.net/?f=T%28-8%2C12%29)
Since in both questions,a and b, we're asked to find lines that are perpendicular to ST. So, we'll do that first!
Perpendicular to ST:
the equation of any line is given by:
where, m is the slope(also known as gradient), and c is the y-intercept.
to find the perpendicular of ST <u>we first need to find the gradient of ST, using the gradient formula.</u>
![m = \dfrac{y_2 - y_1}{x_2 - x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cdfrac%7By_2%20-%20y_1%7D%7Bx_2%20-%20x_1%7D)
the coordinates of S and T can be used here. (it doesn't matter if you choose them in any order: S can be either x_1 and y_1 or x_2 and y_2)
![m = \dfrac{12 - (-4)}{(-8) - 5}](https://tex.z-dn.net/?f=m%20%3D%20%5Cdfrac%7B12%20-%20%28-4%29%7D%7B%28-8%29%20-%205%7D)
![m = \dfrac{-16}{13}](https://tex.z-dn.net/?f=m%20%3D%20%5Cdfrac%7B-16%7D%7B13%7D)
to find the perpendicular of this gradient: we'll use:
![m_1m_2=-1](https://tex.z-dn.net/?f=m_1m_2%3D-1)
both
and
denote slopes that are perpendicular to each other. So if
, then we can solve for
for the slop of ther perpendicular!
![\left(\dfrac{-16}{13}\right)m_2=-1](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B-16%7D%7B13%7D%5Cright%29m_2%3D-1)
:: this is the slope of the perpendicular
a) Line through S and Perpendicular to ST
to find any equation of the line all we need is the slope
and the points
. And plug into the equation: ![(y - y_1) = m(x-x_1)](https://tex.z-dn.net/?f=%28y%20-%20y_1%29%20%3D%20m%28x-x_1%29)
side note: you can also use the
to find the equation of the line. both of these equations are the same. but I prefer (and also recommend) to use the former equation since the value of 'c' comes out on its own.
![(y - y_1) = m(x-x_1)](https://tex.z-dn.net/?f=%28y%20-%20y_1%29%20%3D%20m%28x-x_1%29)
we have the slope of the perpendicular to ST i.e ![m=\dfrac{13}{16}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7B13%7D%7B16%7D)
and the line should pass throught S as well, i.e
. Plugging all these values in the equation we'll get.
![(y - (-4)) = \dfrac{13}{16}(x-5)](https://tex.z-dn.net/?f=%28y%20-%20%28-4%29%29%20%3D%20%5Cdfrac%7B13%7D%7B16%7D%28x-5%29)
![y +4 = \dfrac{13x}{16}-\dfrac{65}{16}](https://tex.z-dn.net/?f=y%20%2B4%20%3D%20%5Cdfrac%7B13x%7D%7B16%7D-%5Cdfrac%7B65%7D%7B16%7D)
![y = \dfrac{13x}{16}-\dfrac{65}{16}-4](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B13x%7D%7B16%7D-%5Cdfrac%7B65%7D%7B16%7D-4)
![y=\dfrac{13x}{16}-\dfrac{129}{16}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B13x%7D%7B16%7D-%5Cdfrac%7B129%7D%7B16%7D)
this is the equation of the line that is perpendicular to ST and passes through S
a) Line through T and Perpendicular to ST
we'll do the same thing for ![T(-8,12)](https://tex.z-dn.net/?f=T%28-8%2C12%29)
![(y - y_1) = m(x-x_1)](https://tex.z-dn.net/?f=%28y%20-%20y_1%29%20%3D%20m%28x-x_1%29)
![(y -12) = \dfrac{13}{16}(x+8)](https://tex.z-dn.net/?f=%28y%20-12%29%20%3D%20%5Cdfrac%7B13%7D%7B16%7D%28x%2B8%29)
![y = \dfrac{13x}{16}+ \dfrac{104}{16}+12](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B13x%7D%7B16%7D%2B%20%5Cdfrac%7B104%7D%7B16%7D%2B12)
![y = \dfrac{13x}{16}+ \dfrac{37}{2}](https://tex.z-dn.net/?f=y%20%3D%20%5Cdfrac%7B13x%7D%7B16%7D%2B%20%5Cdfrac%7B37%7D%7B2%7D)
this is the equation of the line that is perpendicular to ST and passes through T